2007
DOI: 10.3171/jns-07/09/0586
|View full text |Cite
|
Sign up to set email alerts
|

Wilms tumor 1 expression in malignant gliomas and correlation of +KTS isoforms with p53 status

Abstract: The presence of WT1 in glioma cell lines and the majority of primary tumor samples and its absence in normal astrocytes support the suggestion that WT1 expression is important in glioma biology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 36 publications
1
35
0
Order By: Relevance
“…3 It was reported in follow-up work that there was an interaction between the KTS + isoform of WT1 and wild-type p53, revealing that the potential oncogenic function of WT1 in GBM may depend on this splicing variant. 7 Additional avenues whereby WT1 promotes tumorigenesis was found in WT1's relation with Wilms tumor 1-associated protein (WTAP, also known as pre-mRNAsplicing regulator WTAP). WTAP is a nuclear protein that was isolated through a yeast 2-hybrid screen and has been reported to be overexpressed in GBM cell lines.…”
Section: Gbm and Wilms Tumormentioning
confidence: 99%
See 1 more Smart Citation
“…3 It was reported in follow-up work that there was an interaction between the KTS + isoform of WT1 and wild-type p53, revealing that the potential oncogenic function of WT1 in GBM may depend on this splicing variant. 7 Additional avenues whereby WT1 promotes tumorigenesis was found in WT1's relation with Wilms tumor 1-associated protein (WTAP, also known as pre-mRNAsplicing regulator WTAP). WTAP is a nuclear protein that was isolated through a yeast 2-hybrid screen and has been reported to be overexpressed in GBM cell lines.…”
Section: Gbm and Wilms Tumormentioning
confidence: 99%
“…Recently, our laboratory and others have shifted their focus to the Wilms tumor 1 gene (WT1). [5][6][7][8] WT1 was first isolated in 1990 by Haber et al with their discovery that an internal deletion within an 11p13 zinc finger gene contributes to the development of Wilms tumor, a pediatric kidney malignancy. 10 WT1 was initially thought to be a tumor suppressor gene, but subsequent research uncovered its oncogenic role when it was demonstrated that WT1 can suppress hTERT gene expression and telomerase activity in clear cell renal cell carcinoma.…”
mentioning
confidence: 99%
“…3,6,7,10,11,18,22,[24][25][26][27][28][29][30][31]34,36,38,39,42 We have previously demonstrated WT1 expression in approximately 80% of glioma cell lines and tumor speciNovel report of expression and function of CD97 in malignant gliomas: correlation with Wilms tumor 1 expression and glioma cell invasiveness mens. 5 The predominant WT1 isoform expressed in these cells contained a 17-amino acid peptide coded for by exon 5 and the tripeptide KTS between zinc fingers 3 and 4 (WT1 +/+). Our studies showed that glioma cells that had endogenous WT1 expression relied heavily on this protein for their growth and motility.…”
mentioning
confidence: 99%
“…In our experience expression is similar in primary and secondary tumors but expression can be reduced in recurrent tumors. In addition there is evidence that tumors that contain a Tp53 mutation show reduced WT1 levels compared to Tp53 wild type glioblastomas (Clark et al, 2007). IDH1 R132H antibody expression is found in 4% of primary and in 71% of secondary glioblastoma .…”
Section: Immunohistochemistrymentioning
confidence: 98%